Coaching Athletes with Disabilities - Guidelines and Principles in Training Methodology - Abdullah, Nagoor Meera; Ampofo-Boateng, Koame; Latif, Rozita Abdul; Mat, Hisyam Che (Media Ilmu Keolahragaan Indonesia, 2011)
Artikel ini membahas tentang atlet penyandang cacat dan bagaimana kondisi mereka dapat diadaptiskan dengan kegiatan yang cocok untuk memungkinkan mereka berpartisipasi dalam aktivitas fisik dan olahraga. Tujuan yang diharapkan adalah untuk membantu pelatih dalam melakukan pelatihan untuk para penyandang cacat, 1) Untuk memahami kondisi mereka, 2) Merancang program yang tepat untuk kondisi mereka, 3) Menyoroti hambatan dan kondisi yang mempengaruhi atlet dengan partisipasi penyandang cacat dalam olahraga, terutama yang berkaitan dengan kesehatan, keselamatan dan pertimbangan medis yang pelatih harus memahami dan mengelola hati-hati. Artikel ini menawarkan rekomendasi tentang bagaimana pelatih harus melatih atlet dengan cacat.Kata Kunci: pelatihan atlet kebutuhan khususAbstract The article briefly discusses athletes with disabilities and how their condition can be matched with suitable activities to allow them to participate in physical activity and sports. The article also aims at assisting coaches who conducts training for people with disability to understand their condition first, and then devise programs that are appropriate for their condition. Furthermore, it highlights the barriers and conditions that affect athletes with disabilities participation in sports, especially those related to the health, safety, and medical considerations that coaches should understand and manage carefully. The article offers recommendations on how coaches should train athletes with disability.Keywords: disability athletes coaching